Support from Institutional Agents and Perceptions of Cultural and Institutional Fit Among STEM International Graduate Students in the U.S. - Myers, Scott; Myers, Carrie; Johnson, Catherine; Brazill, Shihua (Journal of International Students, 2023)
This quantitative study aimed to understand the association between different types of support from institutional agents and students’ sense of belonging culturally and structurally at their respective institutions. We used one-of-a-kind primary survey data from a National Science Foundation grant that included nearly 1,000 international graduate students in STEM fields across 12 research institutions in the U.S. Drawing from the theories of cultural synergy and reciprocal adaptation, we proposed that support from all three institutional agents of peers, faculty, and mentors would be important for perceptions of fit but that the cultural aspects of mentor support would emerge as most important. Based on regression findings, we found that all three agents played a positive and statistical role in perceptions of cultural and structural fit. However, the results suggested that peer support played the largest role in promoting better perceptions of a sense of belonging culturally and institutionally.